Determinant Factors and Spatial Distribution of Visceral Leishmaniasis in North Gondar in Selected Hospitals - Melesse, Berhanehiwot; Ayalew, Salie; Abere, Mandefro (Journal of Diseases, 2019)
Introduction: Visceral Leishmaniasis (VL) is a neglected tropical disease caused by Leishmaniasis protozoa, and transmitted by a sand fly vector. Leishmaniasis is distributed in worldwide and affects millions of peoples. Objective: The objective was to assess the prevalence and spatial distribution of VL in North Gondar. Methodology: 369 patients were selected from records or medical charts retrospectively using stratified and systematic sampling techniques. The study used spatial autocorrelation measures and auto logistic regression model. Result: From 369 patients, 313 (84.8%) were infected by VL. The proportion of VL incidence for those who traveled to endemic areas was (70.2%). Male patients accounted a larger proportion (93.2%) compared to female patients (6.8%). Moran’s scatter plot test revealed there is regional clustering on the VL incidence. Local Moron’s Index value of Gondar Zuria, Dembeya, Quara, Metemma, Tach Armachiho, Gondar Town, West Belesa and Adarakay was positive, this showed places that shared boundaries have similar VL incidence (i.e high-high or low-low). From result of local Getis and Ord statistic, positive standardized Z-values of Adarkay, Gondar Town, Metema, Quara, West Belesa and Dembiya showed the places were hot spot. Similarly negative standardized Z values of Gondar Zuria and Tach Armachiho revealed that places were cold spot. The spatial auto logistic regression result revealed that sex, travel history, BMI, rainfall and elevation were the significant factors of VL at 95% confidence level. Conclusion: The prevalence of VL is still very high (84.8%) in North Gondar Zone. VL clustered on endemic districts that shared common boundaries.